2021
DOI: 10.24140/issn.1645-7250.rle50.12
|View full text |Cite
|
Sign up to set email alerts
|

La educación social en los extremos: justicia social y paradojas de la práctica.

Abstract: Recensão crítica do livro de Sánchez-Valverde, C. & Montané López, A. (2020). La educación social en los extremos: justicia social y paradojas de la práctica. Valencia: Institut de Creativitat i Innovacions Educatives da Universidad de Valencia, 169 pp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The discussion we have followed up to this point, then, allows us to theorize the places in the institutions and the institutions as places. Several pedagogical experiences (Bossé & Solé, 2017;Fryd, 2012;Sánchez-Valverde & Montaner, 2020) have shown that acknowledging subjective singularities enables us to offer children and adolescents an educational place on the basis of which we can work toward the construction of relationships that boost their social and cultural integration (ASEDES, 2007). In contrast, institutional homogenization because of stigmatized social categories, in this case, "MENA," can give rise to rejection of socio-educational intervention.…”
Section: Ethical Approvalmentioning
confidence: 99%
“…The discussion we have followed up to this point, then, allows us to theorize the places in the institutions and the institutions as places. Several pedagogical experiences (Bossé & Solé, 2017;Fryd, 2012;Sánchez-Valverde & Montaner, 2020) have shown that acknowledging subjective singularities enables us to offer children and adolescents an educational place on the basis of which we can work toward the construction of relationships that boost their social and cultural integration (ASEDES, 2007). In contrast, institutional homogenization because of stigmatized social categories, in this case, "MENA," can give rise to rejection of socio-educational intervention.…”
Section: Ethical Approvalmentioning
confidence: 99%